Organelle‐Specific Anchored Delivery System Stretching a Reversal of Tumor Hypoxia Microenvironment to a Combinational Chemo‐Photothermal Therapy. (19th December 2021) - Chen, Xuerui; Yin, Xuelian; Zhan, Lin; Zhang, Junfeng; Zhang, Yuxi; Wu, Yinghua; Ju, Jiale; Li, Yajie; Xue, Qianghua; Wang, Xu; Li, Chenchen; Reis, Rui L.; et al.
Abstract: Direct delivery to an organelle‐specific point can boost the efficacy of therapy procedures to new heights. Among other subcellular organelles, mitochondria generate ATP as intracellular powerhouse, and are associated with multiple aspects of tumorigenesis and tumor development. Here, a mitochondrial anchored biomimetic nanoplatform (CZACN) is designed and its reversal of tumor hypoxia microenvironment underlying the mitochondria‐located chemo‐photothermal therapy is studied. After shuttling into cancer cells, therapeutic payloads including cisplatin (CDDP) and Au nanozymes are controllably released in the ATP‐overexpressed mitochondria. CDDP generates O2 −, forms H2 O2 for a chemical fuel in the next reaction, and damages mitochondrial DNA. Meanwhile, the catalase‐like Au nanozymes catalyze the produced hydrogen peroxide for oxygen supply to relieve hypoxic tumor microenvironment, offering cytotoxic singlet oxygen against cancer cells under NIR treatment. As a result of cancer‐cell self‐recognition, mitochondria‐targeted therapy, and photothermal conversion ability, the fabricated CZACNs obtained 89.2 ± 3.70% of tumor growth inhibition under NIR irradiation and constrained the dose‐limiting toxicity of CDDP, as well. These findings reinforce the synergistic effect of organelle‐specific navigation and in situ oxygen self‐sufficiency for combinational chemo‐photothermal therapy. Abstract : Organelle‐specific biomimetic nanoplatforms trigger cascade reaction in mitochondria of cancer cells, where the overexpressed ATP fuels the oxygen self‐sufficiency and facilitates chemo‐photothermal efficiency. Tailored for reversal of tumor hypoxia microenvironment, the organelle‐specific strategy constrains a typical dose‐limiting toxicity of cisplatin. It reinforces the synergistic effect of organelle‐specific navigation and in situ oxygen self‐sufficiency for combinational chemo‐photothermal therapy.